Design, Synthesis, and Anti‐HIV Evaluation of Novel Triazine Derivatives Targeting the Entrance Channel of the NNRTI Binding Pocket. (5th December 2014) - Chen, Xuwang; Meng, Qing; Qiu, Liyun; Zhan, Peng; Liu, Huiqing; De Clercq, Erik; Pannecouque, Christophe; Liu, Xinyong
<x xml:space="preserve">Abstract</x> A novel series of triazine derivatives targeting the entrance channel of the HIV‐1 non‐nucleoside reverse transcriptase inhibitor binding pocket (NNIBP) were designed and synthesized on the basis of our previous work. The results of a cell‐based antiviral screening assay indicated that most compounds showed good‐to‐moderate activity against wild‐type HIV‐1 with EC50 values within the concentration range of 0.0078–0.16 μm (compound DCS‐a4, EC50 = 7.8 nm). Some compounds displayed submicromolar activity against the K103N/Y181C resistant mutant strain (such as compound DCS‐a4, EC50 = 0.65 μm). Molecular modeling studies confirmed that the new compounds could bind into the NNIBP similarly as the lead compound, and the newly introduced flexible heterocycles could occupy the entrance channel effectively. In addition, the preliminary structure–activity relationship and the RT inhibitory assay are presented in this study.